INFLUENCE OF THE PERFORMANCE OF NATIONAL POLICE SERVICE IN PREVENTION OF ORGANIZED CRIMES IN MOMBASA COUNTY, KENYA - KIUNGA, NICKSON (Advances in Social Sciences Research Journal, 2021)
This paper uses data collected for an MA Thesis on influence of the Performance of National Police Service in Prevention of organized Crimes in Mombasa County, Kenya. The study was necessitated by continued rise of criminal gangs despite police service efforts to contain the problem. The study was guided by three specific objectives, but for this paper first and second objectives will be discussed. First, the examined the influence of resource capacity on the performance of national police service in prevention of organized crimes in Mombasa County. Secondly, the study examined the influence of motivation on the performance of national police service in prevention of organized crimes. Thirdly, the last objective assessed the influence of external environment on the performance of National Police Service in prevention of organized crimes in Mombasa County, Kenya. The survey utilized Expectancy theory and Crime Pattern Theory and adopted a descriptive research design employing a mixed method paradigm. The study sample size comprised 306 National Police Service officers (NPS); Directorate of Criminal Investigations (DCI) officers, Kenya Police service (KP), and Administration Police (AP) officers both senior and junior. Qualitative data was analyzed using thematic analysis derived from the study objectives. On the other hand, quantitative data was analyzed through descriptive statistics. According to the findings, 17% of the police officers still undertake operations without intelligence briefing, and that despite the availability of criminal intelligence. Besides, access to criminal intelligence was still a major challenge to 45% of the officers while inter-agency coordination was a rare part of the fight against organized crime to 56% of the officers who were not involved. The findings also revealed that despite the importance of training towards the prevention of organized crime, 33% of police officers did not have access to these trainings. Furthermore, 53% of the officers, cited lack of recognition and motivation that could go a long way in raising performance of the police officers. The study makes two major recommendations; special attention to training and curriculum review that addresses the demands of emerging global security challenges. Secondly, officer’s welfare remains a thorny issue which can potentially stifle any crime prevention initiative. Welfare issues of concern such as merit and fairness in promotions, rewards and other incentives, and better compensation were said to be an integral part of any serious police reform agenda.